Impact of late presentation of HIV infection on short-, mid- and long-term mortality and causes of death in a multicenter national cohort: 2004–2013. Issue 5 (May 2016) - ,; Dalmau, David; Navarro, Maria Luisa; González, Maria Isabel; Blanco, Jose Luis; Garcia, Federico; Iribarren, Jose Antonio; Gutiérrez, Félix; Vidal, Francesc; Gonzalez-Garcia, Juan; Berenguer, Juan; Sobrino, Paz; et al.
Summary: Objectives: To analyze the impact of late presentation (LP) on overall mortality and causes of death and describe LP trends and risk factors (2004–2013). Methods: Cox models and logistic regression were used to analyze data from a nation-wide cohort in Spain. LP is defined as being diagnosed when CD4 < 350 cells/ml or AIDS. Results: Of 7165 new HIV diagnoses, 46.9% (CI95% :45.7–48.0) were LP, 240 patients died. First-year mortality was the highest (aHRLP.vs.nLP = 10.3[CI95% :5.5–19.3]); between 1 and 4 years post-diagnosis, aHRLP.vs.nLP = 1.9(1.2–3.0); and >4 years, aHRLP.vs.nLP = 1.5(0.7–3.1). First-year's main cause of death was HIV/AIDS (73%); and malignancies among those surviving >4 years (32%). HIV/AIDS-related deaths were more likely in LP (59.2% vs. 25.0%; p < 0.001). LP declined from 55.9% (2004–05) to 39.4% (2012–13), and reduced in 46.1% in men who have sex with men (MSM) and 37.6% in heterosexual men, but increased in 22.6% in heterosexual women. Factors associated with LP: sex (ORMEN.vs.WOMEN = 1.4[1.2–1.7]); age (OR31–40.vs.<30 = 1.6[1.4–1.8], OR41–50.vs.<30 = 2.2[1.8–2.6], OR>50.vs.<30 = 3.6[2.9–4.4]); behavior (ORInjectedDrugUse.vs.MSM = 2.8[2.0–3.8]; ORHeterosexual.vs.MSM = 2.2[1.7–3.0]); education (ORPrimaryEducation.vs.University = 1.5[1.1–2.0], ORLowerSecondary.vs.University = 1.3[1.1–1.5]); and geographical origin (ORSub - Saharan.vs.Spain = 1.6[1.3–2.0], ORLatin-American.vs.Spain = 1.4[1.2–1.8]). Conclusions: LP is associated with higher mortality, especially short-term- and HIV/AIDS-related mortality. Mid-term-, but not long-term mortality, remained also higher in LP than nLP. LP decreased in MSM and heterosexual men, not in heterosexual women. The groups most affected by LP are low educated, non-Spanish and heterosexual women. Highlights: Late presentation of HIV (LP) is associated with higher mortality. Short-mid-term mortality is higher in LP, without differences in long-term mortality. LP is associated with short-term mortality due to HIV/AIDS. Malignancies were the main cause of death among patients who survived >4 years. LP is higher among non-Spanish, low educated, and heterosexual women.